Conservation of caribou (Rangifer tarandus) in Canada : an uncertain future - Festa-Bianchet, Marco; Côté, Steeve D.; Ray, Justina C.; Boutin, Stanley A.; Gunn, Anne (Canadian Journal of Zoology, 2020)
Caribou (Rangifer tarandus (L., 1758)) play a central role in the ecology and culture of much of Canada, where they were once the most abundant cervid. Most populations are currently declining, and some face extirpation. In southern Canada, caribou range has retreated considerably over the past century. The ultimate reason for their decline is habitat alterations by industrial activities. The proximate causes are predation and, to a lesser extent, overharvest. The most southerly populations of “Mountain” caribou are at imminent risk of extirpation. Mountain caribou are threatened by similar industrial activities as Boreal caribou, and face increasing harassment from motorized winter recreational activities. Most populations of “Migratory Tundra” caribou are currently declining. Although these caribou fluctuate in abundance over decades, changing harvest technologies, climate change, increasing industrial development and human presence in the North raise doubts over whether recent declines will be followed by recoveries. The Peary caribou (Rangifer tarandus pearyi J.A. Allen, 1902), a distinct subspecies endemic to Canada’s High Arctic, has suffered drastic declines caused by severe weather, hunting and predation. It faces an increasing threat from climate change. While some questions remain about the reasons for the decline of Migratory Tundra caribou, research has clearly identified several threats to the persistence of “Boreal”, Mountain, and Peary caribou. Scientific knowledge, however, has neither effectively influenced policies nor galvanized public opinion sufficiently to push governments into effective actions. The persistence of many caribou populations appears incompatible with the ongoing pace of industrial development. Le caribou (Rangifer tarandus (L., 1758)) occupe une place centrale dans l’écologie et la culture de plusieurs régions du Canada. Bien que le caribou ait déjà été le cervidé le plus abondant au Canada, la plupart des populations sont présentement en déclin et certaines font même face ...